Pediatric primary Sjögren syndrome presenting with bilateral ranulas: A case report and systematic review of the literature. (October 2017) - Means, Casey; Aldape, Mark A.; King, Ericka
Abstract: Context: Primary Sjögren syndrome is uncommon in children, and the standard clinical criteria used in diagnosis of adult Sjögren syndrome will miss many children with the disease. Floor of mouth ranulas have not been described in Sjögren syndrome. Objective: This study aims to describe a novel presentation of juvenile primary Sjögren syndrome, and to present a comprehensive systematic review of the literature regarding the presentation and diagnosis of Sjögren syndrome in children. Data sources: Ovid MEDLINE. Study selection: A MEDLINE literature search was performed using the following search terms: primary, Sjögren, disease, and children. Results were limited to human subjects and articles written in English between 1981 and 2014. Applicable articles were reviewed and qualitatively summarized. Data extraction: Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines (PRIMA). Results: Initial MEDLINE search yielded 146 articles, 80 of which were excluded as not clinically pertaining to Sjögren syndrome. An additional 25 were excluded due to lack of pediatric-specific data. Systematic review of the literature revealed no reports of ranula in association with Sjögren syndrome. 6 papers were manually included from review of reference lists of included articles. Our review indicated that recurrent parotitis is the most commonly reported presenting symptom in children, followed by ocular and oral symptoms, musculoskeletal, and renal symptoms. Compared to adults, children are less likely to present with dry eyes and mouth. Limitations: All studies were retrospective chart reviews, case series or case reports. Conclusion: This is the first report of a child presenting with floor of mouth ranulas in association with Sjögren syndrome. While recurrent parotitis is the most common presentation in children, other salivary gland and extra-salivary manifestations may be seen, and the clinician must maintain a high index of suspicion for underlying Sjögren syndrome.